2012
DOI: 10.1590/s2179-64912012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Chewing time and chewing strokes in different dentofacial deformities

Abstract: PURPOSE: To verify whether the number of chewing strokes and the chewing time are influenced by dentofacial deformities in habitual free mastication. METHODS: Participants were 15 patients with diagnosis of class II dentofacial deformity (GII), 15 with class III (GIII), and 15 healthy control individuals with no deformity (CG). Free habitual mastication of a cornstarch cookie was analyzed, considering the number of chewing strokes and the time needed to complete two mastications. Strokes were counted by consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Changes related to chewing, swallowing and speech were found in the orofacial functions studied in all of investigated DFD individuals. Several authors have described changes in orofacial functions in patients with class II and III malocclusion (10,15,17,26) , similar to that seen in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Changes related to chewing, swallowing and speech were found in the orofacial functions studied in all of investigated DFD individuals. Several authors have described changes in orofacial functions in patients with class II and III malocclusion (10,15,17,26) , similar to that seen in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The dorsum of the tongue is used to crush food against the palate and there is also little or no action of the buccinator muscles. Cases with class II and III malocclusion were compared to a control group and showed abnormalities in the chewing efficiency, although the authors have not found differences between individuals with the deformity (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Measurement methods of chewing cycles reported include surface electromyography (28,29), motion capture (30,31), kinesiograph (32) and visual examination (22,23). The number of chewing cycles are measured based on myoelectric waveforms in surface electromyograms, and the trajectory of mandibular movements in motion capture and kinesiograph.…”
Section: Discussionmentioning
confidence: 99%
“…The chewing movement data has been collected with the proposed method and a video camera, simultaneously and compared with the clinical assessment. We recorded the experiment with a camera (D3100 Nikon) to check the information acquired in the clinical evaluation that has been validated in the literature [29] .…”
Section: Methodsmentioning
confidence: 99%